2019
DOI: 10.1002/hipo.23169
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness predicts effective connectivity between the hippocampus and default mode network nodes in young adults

Abstract: Rodent and human studies examining the relationship between aerobic exercise, brain structure, and brain function indicate that the hippocampus (HC), a brain region critical for episodic memory, demonstrates striking plasticity in response to exercise.Beyond the hippocampal memory system, human studies also indicate that aerobic exercise and cardiorespiratory fitness (CRF) are associated with individual differences in large-scale brain networks responsible for broad cognitive domains. Examining network activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 109 publications
(188 reference statements)
2
26
0
1
Order By: Relevance
“…Brain connectivity and mental health have been associated with cardiorespiratory fitness. 23,24 Recently, Plá cido et al 10 found a strong association among cardiorespiratory fitness measured through the 2-minute step test, Alzheimer's disease (AD), and mild cognitive impairment (MCI). The authors showed that people at risk of functional loss were most likely to be diagnosed with mild (OR = 10.7; p = 0.001) to moderate (OR = 14.7; p = 0.002) AD, whereas individuals with low aerobic fitness were 4.5 times more likely to present with MCI (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain connectivity and mental health have been associated with cardiorespiratory fitness. 23,24 Recently, Plá cido et al 10 found a strong association among cardiorespiratory fitness measured through the 2-minute step test, Alzheimer's disease (AD), and mild cognitive impairment (MCI). The authors showed that people at risk of functional loss were most likely to be diagnosed with mild (OR = 10.7; p = 0.001) to moderate (OR = 14.7; p = 0.002) AD, whereas individuals with low aerobic fitness were 4.5 times more likely to present with MCI (p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Physical fitness and cognition in elders brain regions, such as the medial prefrontal cortex and default mode network (DMN), 23 explaining the link between physical capacity and improved cognition and depression. The hippocampus and DMN are closely associated to cognition and depression, 23,26 reinforcing the perspective of physical fitness improving mental health. This is relevant because persons living in LTCFs have poor physical fitness and high physical dependence, which could be associated to poor mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing at the Boston University Fitness and Recreation Center, study staff instructed participants to refrain from aerobic exercise and/or resistance training for 24 hr prior to testing and refrain from any caffeine consumption for 3 hr prior to testing. The incremental treadmill test protocol implemented by our laboratory (Kronman et al, 2020; Nauer, Dunne, et al, 2020; Nauer, Schon, & Stern, 2020) includes three phases: 3 min of warm‐up, approximately 8–12 min of incremental exercise, and 3 min of cool‐down. Throughout the duration of the test, a study staff member monitored the participant's heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ezama et al (2021) found that during the resting-state, anterior sections of the hippocampus coactivated with brain regions typically associated with the somatomotor network, whereas middle/posterior sections of the hippocampus co-activated with brain regions typically associated with the default mode network. Thus, whereas previous studies have shown that PA affects the connectivity between the hippocampus and the default mode network (Kronman et al, 2020;Stillman et al, 2018;Raichlen et al, 2016), how PA is associated to the connectivity between the hippocampus and the somatomotor networks remains unknown.…”
Section: Introductionmentioning
confidence: 95%